Changes in the Area per Lipid Molecule by P–V–T and SANS Investigations. Issue 1 (January 2014) - Soloviov, Dmitry; Zabashta, Yuriy; Bulavin, Leonid; Olexandr, Ivankov; Gordeliy, Valentin; Kuklin, Alexander; Bulavin, Leonid; Guenet, Jean‐Michel
Summary This paper describes the study of lipid DPPC, carried out on setup for simultaneous investigations by P–V–T and SANS methods. The data allowed us to calculate in area per lipid molecule changes during the lipid phase transition from ripple phase to liquid‐crystalline phase.